Complaint Management Strategy in Dealing with Allegations of Malpractice in the Digital Age - Mahardhika, Rosliana; Sumarwanto, Edi; Rosa, Elsye Maria (LP2M INSURI Ponorogo, 2023)
In Indonesia, there has been a rise in the number of suspected medical malpractice cases, causing tangible harm to patients and undermining trust in the healthcare system. To address this growing concern in the digital era, this study aims to identify effective hospital strategies for handling complaints arising from alleged malpractice incidents. A systematic literature review was conducted, utilizing international and national databases to select and search for pertinent information on hospital complaint-handling processes and strategies in the digital era. The study underscores the significance of establishing a comprehensive complaint-handling system in hospitals to address increasing complaints. Key strategies identified include preparing professional resources dedicated to handling complaints, enhancing awareness regarding patient safety, and ensuring strict adherence to existing Standard Operating Procedures (SOPs). By adopting the identified strategies, hospitals can mitigate the adverse effects of medical accidents, improve patient safety, and rebuild trust between patients and medical personnel in the digital era.